Impact of Enhanced Anchored Instruction in Inclusive Math Classrooms. (January 2015) - Bottge, Brian A.; Toland, Michael D.; Gassaway, Linda; Butler, Mark; Choo, Sam; Griffen, Ann Katherine; Ma, Xin
The Common Core State Standards for Mathematics will place more pressure on special education and math teachers to raise the skill levels of all students, especially those with disabilities in math (MD). The purpose of this study was to assess the effects of enhanced anchored instruction (EAI) on students with and without MD in co-taught general education classrooms. Results showed that students in the EAI condition improved their performance on math skills contained in several of the standards. Effect sizes were especially large for students with MD when the special education teacher more actively participated in the instructional activities with the math teacher. Classroom observations provided examples of how teachers can work together to benefit students in inclusive math settings.